2021
DOI: 10.1177/08971900211004840
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Usage and Dosing of Guideline-Directed Medical Therapy for Heart Failure With Reduced Ejection Fraction Patients in Clinical Practice

Abstract: Background: Although strategies for optimization of pharmacologic therapy in patients with heart failure with reduced ejection fraction (HFrEF) are scripted by guidelines, data from HF registries suggests that guideline-directed medical therapies (GDMT) are underutilized among eligible patients. Whether this discrepancy reflects medication intolerance, contraindications, or a quality of care issue remains unclear. Objective: The objective of this initiative was to identify reasons for underutilization and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
6
1
1
Order By: Relevance
“…On the other hand, ARNI therapy was observed to be importantly underused, and this action was similar to the results of registry-based studies such as the CHAMP-HF registry (13%) but lower than that reported in the study of Smith et al (27%) [24,25]. Regarding the history of this medication, the US Food and Drug Administration (FDA) approved the ARNI sacubitril/valsartan (S/V) for patients with HFrEF in July 2015 after the important results of the PARADIGM-HF trial, in which S/V reduced the risk of cardiovascular death or hospitalization for HF in 20% compared to placebo [26].…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, ARNI therapy was observed to be importantly underused, and this action was similar to the results of registry-based studies such as the CHAMP-HF registry (13%) but lower than that reported in the study of Smith et al (27%) [24,25]. Regarding the history of this medication, the US Food and Drug Administration (FDA) approved the ARNI sacubitril/valsartan (S/V) for patients with HFrEF in July 2015 after the important results of the PARADIGM-HF trial, in which S/V reduced the risk of cardiovascular death or hospitalization for HF in 20% compared to placebo [26].…”
Section: Discussionsupporting
confidence: 81%
“…Estimates suggest many patients with heart failure with reduced ejection fraction (HFrEF) are not prescribed recommended medications, despite compelling evidence demonstrating decreased mortality and hospitalisations with improved quality of life 1–8 . Researchers have previously explored reasons for suboptimal prescribing for HFrEF and identified multifactorial issues that persist among primary care and cardiology settings 5,8–11 .…”
Section: Introductionmentioning
confidence: 99%
“…Estimates suggest many patients with heart failure with reduced ejection fraction (HFrEF) are not prescribed recommended medications, despite compelling evidence demonstrating decreased mortality and hospitalisations with improved quality of life. [1][2][3][4][5][6][7][8] Researchers have previously explored reasons for suboptimal prescribing for HFrEF and identified multifactorial issues that persist among primary care and cardiology settings. 5,[8][9][10][11] These issues include clinical inertia (i.e., delayed intervention or treatment to target), 12 cost, fear of adverse effects, clinician knowledge, and competing patient priorities.…”
Section: Introductionmentioning
confidence: 99%
“…The role of cardiac sympathetic hyperactivation in HF is highlighted by the use of β-blockers and cardiac sympathetic denervation as the key approach to the current therapy of HF [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. However, such pharmacological treatment may not be ideal because some studies have demonstrated that β-blockers do not provide satisfactory protection against sudden cardiac death, and some patients are either intolerant or refractory to this therapy [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Additionally, despite being an alternative in managing refractory ventricular arrhythmias [ 38 , 43 , 51 , 52 ], cardiac sympathetic denervation has adverse complications (including Horner’s syndrome, hyperhidrosis, paresthesia, and sympathetic fight/fight response loss) that severely limit the use of procedures in HF patients [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%